AKTUALISASI NILAI-NILAI AL-QUR’AN DALAM MEWUJUDKAN KERUKUNAN DAN PERDAMAIAN ANTAR UMAT MANUSIA - Baihaki, Egi Sukma (Dialogia: Jurnal Studi Islam dan Sosial, 2016)
Abstract: Al-Qur'an is as Moslem guidance that taught more values.  Recently, many more wars, conflicts, and dissensions are disharmony the social interaction. Those accidents brought religion to legitimate its actions and the verses of Qur’an are also used to excuse those ones. This paper explains how the values in Qur’an can be realized to construct human life peaceful